Cultural Perspectives on Aging - Hülsen-Esch, Andrea (De Gruyter, 2021)
The societal significance of old age and ageing are increasing due to demographic developments. Age(ing) is not only a biological and social fact, but also a cultural one. This book reveals the importance of cultural factors in order to build a framework for analyzing and understanding cultural constructions of ageing, bringing together scholarly discourses from the arts and humanities as well as social, medical and psychological fields of study.